Development Boneythings Store E-Commerce Application for Selling Muslimah Clothes - Nurainun; Yulianto; Emil Riza Putra (TEPIAN, 2022)
The background of this research is because it can make it easier for a seller to introduce or market their products, and this website, can save costs and be more efficient. Therefore, the purpose of this study is to provide convenience to store owners and consumers in obtaining information purchasing products sold by the Web-Based Boneythings Store. The tools used in drawing the system model are in the form of use cases, activity diagrams, class diagrams, sequence diagrams. To implement this application, sales and orders are needed, supporting components are needed to work properly. These components include using the PHP programming language and for data storage using a MySQL database. The design of this system is expected to help and overcome existing problems so that it can be useful for interested parties.